2020
DOI: 10.5465/amj.2017.1335
|View full text |Cite
|
Sign up to set email alerts
|

“And Who Are You?”: A Performative Perspective on Authority in Organizations

Abstract: As work and organizational reality become increasingly "post-bureaucratic," the conventional and stable bases of a person's authority-their position, their expertise, or the acquiescence of a subordinate-are eroding. This evolution calls us to revise our understanding of authority, and to consider more deeply how it is achieved in contexts that are both fluid and fragmented. Building on a six-month autoethnography of a consulting assignment, we show that authority is a practical, relational, and situated perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 93 publications
3
75
0
2
Order By: Relevance
“…First, the first author kept a sibylline research diary (Laszczuk & Garreau, 2018) over the period of observation that allowed to take notes systematically and to share it with the second author (e.g. Bourgoin, Bencherki, & Faraj, 2019;Bourgoin & Harvey, 2018). The data collection setup allowed for assistance and participation in 98 events of NOP development over 60 months and for the recording of a substantial part of it (45 events, representing 68 h of audio recordingssee Appendix 1).…”
Section: Data Collectionmentioning
confidence: 99%
“…First, the first author kept a sibylline research diary (Laszczuk & Garreau, 2018) over the period of observation that allowed to take notes systematically and to share it with the second author (e.g. Bourgoin, Bencherki, & Faraj, 2019;Bourgoin & Harvey, 2018). The data collection setup allowed for assistance and participation in 98 events of NOP development over 60 months and for the recording of a substantial part of it (45 events, representing 68 h of audio recordingssee Appendix 1).…”
Section: Data Collectionmentioning
confidence: 99%
“…Given our role in convening and facilitating the events we report on, we do not wish to erase or overlook our own involvement in the overall process. In line with scholars adopting an action-research approach (Robertson, 2000) and encouraged by recent studies assuming a similar posture (e.g., Bourgoin et al, 2019), we embrace our participation and approach it with a reflexive stance to account for our part in shaping the situations we describe (see Cunliffe, 2003;Macbeth, 2001). For instance, we appear in the video and audio data we analyzed, and pondered for a long time on how to account for our dual role (Brannick and Coghlan, 2007;Davis, 1973).…”
Section: Methodsmentioning
confidence: 66%
“…Importantly, with such a move toward a constitutive understanding of communication for the existence and perpetuation of organizations as collective actors, we believe that PR scholarship has a unique chance to build further inroads into the larger field of organization and management studies-similar to the ways in which organizational communication scholarship has found increasing recognition in organization and management studies over the past years (e.g. Ashcraft et al, 2009;Bourgoin et al, 2020;Cooren et al, 2011, Koschmann et al, 2012Schoeneborn et al, 2019). At the same time, a constitutive view has also found increasing resonance in PR scholarship lately (e.g.…”
Section: Discussionmentioning
confidence: 97%